Relationship between blood flow, thrombus, and neointima in stents - Richter, Götz Martin; Nöldge, Gerd (Journal of vascular and interventional radiology, 2008)
PURPOSE: To establish a relationship between flow, acute thrombus formation, and late intimal hyperplasia in arterial stents. MATERIALS AND METHODS: To compare short-term stent patency in the canine femoral artery with normal flow to that in the opposite femoral artery with restricted flow, 24 dogs were subdivided in four groups: groups 1 (no intravenous heparin) and 2 (intravenous heparin) had unilateral flow restriction by surgically created stenosis, downstream of a Palmaz stent. Group 3 (no intravenous heparin) and 4 (intravenous heparin) had sham surgical exposure of the corresponding arterial segment, without flow restriction. Thrombocyte activity over the stent segment was evaluated for 3 hours after stent placement with nuclear scanning, after administration of indium-111-labeled platelets. To evaluate long-term stent patency in relationship to arterial flow, 14 additional dogs were subjected to long-term observation. Matched, symmetrically implanted femoral stents with normal and restricted flow, were explanted at 1, 12, and 24 weeks for histologic analysis and comparative measurement of neointimal thickness. Angiographic studies were performed before and after nuclear scanning in the short-term study group and before explant in the long-term animal group. RESULTS: In the short-term, groups 2 and 4 showed neither increased platelet uptake nor angiographically demonstrable thrombus. Group 1 had increased platelet uptake and occlusive or subocclusive angiographic thrombus. Group 3 had increased platelet uptake and angiographic thrombus in one instance. In the long-term, stents with flow restriction had significantly greater neointimal formation in comparison with unrestricted stents. Histologic studies suggested that the stent neointima resulted from progressive replacement of stent thrombus. CONCLUSION: Regardless of flow condition, intravenous heparinization is necessary to prevent thrombus formation in the stent lumen. Within the experimental parameters of this study, low flow and absent heparinization consistently lead to stent thrombosis. Stent implantation under low flow is associated with increased neointima formation. It is not known whether this is preventable by antithrombotic medication.